The influence of workplace culture on nurses' learning experiences: a systematic review of qualitative evidence. (June 2016) - Davis, Kate; White, Sarahlouise; Stephenson, Matthew
EXECUTIVE SUMMARY: Background: A healthy workplace culture enables nurses to experience valuable learning in the workplace. Learning in the workplace enables the provision of evidence-based and continuously improving safe patient care, which is central to achieving good patient outcomes. Therefore, nurses need to learn within a workplace that supports the implementation of evidence-based, professional practice and enables the best patient outcomes; the influence of workplace culture may play a role in this. Objectives: The purpose of this review was to critically appraise and synthesize the best available qualitative evidence to understand both the nurses' learning experiences within the workplace and the factors within the workplace culture that influence those learning experiences. Inclusion criteria Types of participants : Registered and enrolled nurses regulated by a nursing and midwifery board and/or recognized health practitioner regulation agency (or their international equivalent). Phenomena of interest : This review considered studies that described two phenomena of interest: the nurses' learning experience, either within an acute healthcare workplace or a workplace-related learning environment and the influence of workplace culture on the nurses' learning experience (within the workplace or workplace-related learning environment). Context : This review considered studies that included nurses working in an acute healthcare organization within a Western culture. Types of studies : This review considered studies that focused on qualitative evidence and included the following research designs: phenomenological, grounded theory and critical theory. Search strategy: Published and unpublished studies in English from 1980 to 2013 were identified using a three-step search strategy, searching various databases, and included hand searching of the reference lists within articles selected for appraisal. Methodological quality: For studies meeting the inclusion criteria, methodological quality was assessed using a standardized checklist from the Joanna Briggs Institute Qualitative Assessment and Review Instrument (JBI-QARI). Data extraction: Qualitative data were extracted from articles included in the review using the standardized data extraction tool from the JBI-QARI. Data synthesis: Qualitative research findings were pooled using the Joanna Briggs Institute Qualitative Appraisal and Review Instrument (JBI-QARI). This involved the aggregation and synthesis of findings to generate a set of categories, which were then subjected to a meta-synthesis to produce a single comprehensive set of synthesized findings that could be used as a basis for evidence-based practice. Results: Fourteen articles were identified following appraisal and a total of 105 findings (85 unequivocal and 20 credible) were extracted from included studies and grouped into eight categories based on similarity of meaning. Subsequently, categories were grouped into two synthesized findings. The two synthesized findings were as follows: Organizational influences : Enabling nurses to demonstrate accountability for their own learning, along with clear organizational systems that provide resources, time, adequate staffing and support, demonstrates encouragement for and the value of nurses' learning and education. Relational dynamics : Nurses value their peers, expert nurses, preceptors, mentors and educators facilitating and encouraging their learning and professional development. Conclusion: An optimal workplace culture is central for nurses to experience valuable and relevant learning in the workplace. To emphasize the importance of nurses' learning in the workplace, working and learning is understood as an integrated experience. Consequently, a dual system that enables nurses to demonstrate accountability for their own learning, along with clear organizational and educational systems, is required to demonstrate the value in nurses' learning and education.